VILLAGE INSTITUTIONAL COMMUNICATION SYSTEM IN JATIMULYA VILLAGE - liska uaneto; Sudarsono; sitti djou (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The purpose of the study was to find out about the Institutional Communication System of the Village Consultative Body in Jatimulya Village. The research method used is the type of research used is descriptive research. While the research approach used is a qualitative approach. The results showed that 1) The cultural communication system at the BPD Institution in Jatimulya Village had not run well because there was still an unfinished emotional connection. 2) The social communication system at the BPD Institution in Jatimulya Village has not gone well, because there are still individual traits such as selfishness in managing institutions. 3) The intra and interpersonal communication system at the BPD Institution in Jatimulya Village is running well, because this will affect both institutional and personal psychology. 4) The organizational communication system at the BPD Institution in Jatimulya Village on the quality of work caused by communication that does not go well other than by looking at the work targets that must be completed not on time.